Morbillivirus Infections: An Introduction - De Vries, Rory; Duprex, W.; De Swart, Rik (Viruses, 2015)
Research on morbillivirus infections has led to exciting developments in recent years. Global measles vaccination coverage has increased, resulting in a significant reduction in measles mortality. In 2011 rinderpest virus was declared globally eradicated – only the second virus to be eradicated by targeted vaccination. Identification of new cellular receptors and implementation of recombinant viruses expressing fluorescent proteins in a range of model systems have provided fundamental new insights into the pathogenesis of morbilliviruses, and their interactions with the host immune system. Nevertheless, both new and well-studied morbilliviruses are associated with significant disease in wildlife and domestic animals. This illustrates the need for robust surveillance and a strategic focus on barriers that restrict cross-species transmission. Recent and ongoing measles outbreaks also demonstrate that maintenance of high vaccination coverage for these highly infectious agents is critical. This introduction briefly summarizes the most important current research topics in this field.